Influence of fatigue on race walking stability - Neumann, H. F.; Krug, J.; Gohlitz, D. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
In competition race walkers have to demonstrate ground contact and knee straightening stable although the coordination of the body segments varies. The aim of this study was to investigate the stability of the movement structure adhering to the rules under the influence of increasing fatigue. Four female race walkers of the National Junior Team performed two training sessions on a treadmill. With the help of video analysis and dynamometric platforms underneath the treadmill relevant gait variables of all steps could be analyzed. Although velocity and performance level of the four athletes were comparable, the results showed individual characteristics of stability - variability of the movement structure and individual compensating effects under increasing fatigue.